ANALYSIS OF THE IMPLEMENTATION OF PTPN 1 REGIONAL 7 CSR PROGRAM ON ECONOMIC DEVELOPMENT IN THE SUMBAGSEL REGION - Febriana, Vonnyca; Oktaviannur, M. (Penerbit Lafadz Jaya, 2024)
This study examines t,he implementation of the Corporate Social Responsibility (CSR) program by PTPN I Regional 7, specifically the Micro and Small Business Funding Program (PUMK), in the Southern Sumatra region. Using a descriptive qualitative approach, the research explores the program's impact on micro, small, and medium enterprises (MSMEs) and local economic development. Data collection involved interviews, document analysis, and stakeholder observations, including beneficiaries and company representatives. The findings reveal that the PUMK program has successfully increased access to capital, provided training, and created job opportunities, particularly in Lampung, South Sumatra, and Bengkulu. However, implementation in South Sumatra lags behind other regions due to challenges such as limited information dissemination and low managerial capacity among MSME actors. Strategic collaboration with Bank Rakyat Indonesia (BRI) has significantly improved program reach and impact. Despite these successes, further evaluation and efforts are necessary to address existing challenges and optimize the program’s effectiveness. Enhancing digital access, increasing loan ceilings, and integrating environmental sustainability are recommended to ensure broader and more sustainable impacts.